When deriving the natural level of output i am confused as to how the leap is made in the last two lines.(adsbygoogle = window.adsbygoogle || []).push({});

P = P(1+μ)F(1-Y/L,z) =>

1 = (1+μ)F(1-Y/L,z) =>

Y_{n}=h(μ,L,z)

I understand how the mark-up, Total Labour and variable factors are the factors of the natural level but how does this come from the above line?

Thanks,

Josh

**Physics Forums - The Fusion of Science and Community**

# The Algebra for Theory of Natural Output

Have something to add?

- Similar discussions for: The Algebra for Theory of Natural Output

Loading...

**Physics Forums - The Fusion of Science and Community**